2013
DOI: 10.1021/jp403158z
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Photoionization of Fluorenyl, Benzhydryl, Diphenylmethylene, and Their Dimers

Abstract: Two π-conjugated radicals, fluorenyl (C13H9) and benzhydryl (C13H11), as well as the carbene diphenylmethylene (C13H10) were studied by imaging photoelectron-photoion coincidence spectroscopy using VUV synchrotron radiation. The reactive intermediates were generated by flash pyrolysis from 9-bromofluorene and α-aminodiphenylmethane (adpm), respectively. Adiabatic ionization energies (IEad) for all three species were extracted. Values of 7.01 ± 0.02 eV for fluorenyl and 6.7 ± 0.1 eV for benzhydryl are reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…12 We emphasize that the degree of secondary reactions in the reactor can be controlled by several parameters, such as the precursor concentration, lengths of the SiC tube, pyrolysis temperature, and backing gas pressure. While in a continuous expansion at low pressure significant dimerization takes place, 20,24 it can in principle be suppressed in a pulsed jet. However, in the present experiments we deliberately maintained conditions that favour bimolecular reactions and observed them by choosing a suitable delay between laser and pulsed valve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 We emphasize that the degree of secondary reactions in the reactor can be controlled by several parameters, such as the precursor concentration, lengths of the SiC tube, pyrolysis temperature, and backing gas pressure. While in a continuous expansion at low pressure significant dimerization takes place, 20,24 it can in principle be suppressed in a pulsed jet. However, in the present experiments we deliberately maintained conditions that favour bimolecular reactions and observed them by choosing a suitable delay between laser and pulsed valve.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed information on reaction products is obtained, when ions and photoelectrons are detected in coincidence. [24][25][26] We recently showed that IR/UV ion dip spectroscopy is a powerful, alternative tool to study high temperature reactions in a flow reactor, since it combines the structural sensitivity of infrared spectroscopy with mass information. 27,28 In this technique, molecules are ionised by [1+1] resonance-enhanced multiphoton ionisation (REMPI) with UV laser radiation.…”
Section: Introductionmentioning
confidence: 99%
“…ESR spectra have been measured for both radicals in solution. 34,35 Fischer and co-workers characterized the indenyl 36 and fluorenyl 37 radicals and their cations by threshold photoionization spectroscopy. In an inert gas matrix, visible absorption and emission of indenyl have been observed but not assigned, 38 while a combined Raman, FTIR, and UV/Vis study was carried out on fluorenyl.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon‐centered radicals are ubiquitous species involved in numerous chemical reactions such as combustion, radical‐induced polymerization and photochemistry . Their paramagnetic properties allow for their direct observation by EPR spectroscopy, as well as other spectroscopic techniques such as UV/visible spectroscopy for conjugated systems incorporating such centers .…”
Section: Introductionmentioning
confidence: 99%